2015
DOI: 10.1186/s12885-015-1402-y
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated cholinergic network as a novel biomarker of poor prognostic in patients with head and neck squamous cell carcinoma

Abstract: BackgroundIn airways, a proliferative effect is played directly by cholinergic agonists through nicotinic and muscarinic receptors activation. How tumors respond to aberrantly activated cholinergic signalling is a key question in smoking-related cancer. This research was addressed to explore a possible link of cholinergic signalling changes with cancer biology.MethodsFifty-seven paired pieces of head and neck squamous cell carcinoma (HNSCC) and adjacent non-cancerous tissue (ANCT) were compared for their mRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 66 publications
(71 reference statements)
0
17
0
Order By: Relevance
“…Among the key prognostic markers for survival, epidermal growth factor receptor (EGFR), cyclin D1(CCND1), ERCC1, p16, human papillomavirus (HPV), and B‐cell lymphoma‐extra large (Bcl‐xL)/Bcl‐2, as well as the amplification of genes including EMS1 , FGFR1 , and CCND1 have demonstrated some evidence in clinical trials. Others are slower to advance in clinical development because of unconvincing data and few published studies; for example, acetylcholinesterase(AchE), SNPs of specific genes, glutathione S‐transferase (GST), CD44, amplification of specific genes, hypoxic markers, KLK‐6, and MDA‐7/IL‐24; although, this does not preclude them from future investigations and clinical utility.…”
Section: Biomarkers In Hnscc Tumor Tissuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the key prognostic markers for survival, epidermal growth factor receptor (EGFR), cyclin D1(CCND1), ERCC1, p16, human papillomavirus (HPV), and B‐cell lymphoma‐extra large (Bcl‐xL)/Bcl‐2, as well as the amplification of genes including EMS1 , FGFR1 , and CCND1 have demonstrated some evidence in clinical trials. Others are slower to advance in clinical development because of unconvincing data and few published studies; for example, acetylcholinesterase(AchE), SNPs of specific genes, glutathione S‐transferase (GST), CD44, amplification of specific genes, hypoxic markers, KLK‐6, and MDA‐7/IL‐24; although, this does not preclude them from future investigations and clinical utility.…”
Section: Biomarkers In Hnscc Tumor Tissuesmentioning
confidence: 99%
“…FGFR1,22 and CCND1 91-93 have demonstrated some evidence in clinical trials. Others are slower to advance in clinical development because of unconvincing data and few published studies; for example, acetylcholinesterase(AchE),64 SNPs of specific genes,19 glutathione S-transferase (GST),54 CD44,61 amplification of specific genes, 32 hypoxic markers, 35,94 KLK-6,60 and MDA-7/IL-24 72 ; although, this does not preclude them from future investigations and clinical utility.…”
mentioning
confidence: 99%
“…A proliferative effect is played directly by cholinergic agonists at nAChRs. Castillo-González et al [10] found that low expression of acetylcholine esterase, as a key protein in the non-neuronal cholinergic system, is associated with low prognosis and shorter survival by signaling downstream events that may favor tumor growth and aggressiveness. nAChRs of a different subunit composition lead to different signaling mechanisms [11].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies recently have revealed that ACh also plays a non-neuronal role in some physiological and pathological process including inflammatory diseases89, functional bowel disorders1011, as well as several kinds of cancer1213. Several reports have indicated that ACh could act as a potential growth factor to stimulate cancer cell proliferation in lung cancer14, breast cancer15, colon cancer16 et al .…”
mentioning
confidence: 99%